Bride ales and penny weddings recreations, reciprocity, and regions in Britain from the sixteenth to the nineteenth century - Houston, Robert Allan 1954- (Oxford Univ. Press, 2014)
This title looks at regionally distinctive practices of wedding traditions in Britain from the 16th to the 19th centuries, in order to understand social networks, community attitudes, and local and regional identities